National Nuclear Security Threat Assessment, Design Basis Threats and Representative Threat Statements : Implementing guide - International Atomic Energy Agency; Vienna, 2021.; International Atomic Energy Agency (Vienna : International Atomic Energy Agency, 2021)
.
"STI/PUB/1926" --Title page verso.
"May 2021" --Title page verso.
Includes bibliographical references.
Also available online.
Keywords: Risk assessment; Nuclear facilities -- Security measures; Radioactive substances -- Security measures